A Systematic Study of the Reactive In Situ Synthesis of Self-Assembled Silver Nanoparticles on Cotton Yarn - Hamed Mohammadi Mofarah; Mutalifu Abulikemu; Hyung Woo Choi; Ghassan E. Jabbour (Textiles)
Silver nanoparticles (AgNPs) have attracted considerable interest for various applications, including antiviral and antimicrobial treatments, textile nanocomposites, heat transfer and strain sensing textiles, flexible electronics, and smart textiles. Their unique properties, determined by their size, shape, and morphology, render them suitable for a wide range of uses, such as antimicrobial treatments, anticancer therapy, drug delivery, personal protective equipment (PPE), and catalysis. In this investigation, we present an in situ reactive technique for the self-assembly of AgNPs directly onto cotton yarn. A systematic investigation was undertaken to establish the influence of several synthesis parameters on the average size of AgNPs. The variables under consideration included the ambient vacuum conditions, the concentration of both Ag precursor and reducing agent, the growth temperature, and the duration of thermal treatment. By precisely optimizing these parameters, we successfully regulated the AgNPs size range between 10 and 50 nm on the cotton yarn. The findings of this study elucidate the methodology of the controlled synthesis of AgNPs on cotton yarn for potential advancements in smart textile technologies.